2006
DOI: 10.1124/jpet.106.112326
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Suppression of Plasma Testosterone Levels and Tumor Growth in the Dunning Rat Model Treated with Degarelix, a New Gonadotropin-Releasing Hormone Antagonist

Abstract: Degarelix (FE 200486) is a member of a new class of water-soluble (>50 mg/ml) gonadotropin-releasing hormone (GnRH) antagonists in clinical development for prostate cancer. Upon subcutaneous administration, degarelix forms a gel that results in a sustained release of the compound into the circulation, immediately blocking GnRH receptors in the pituitary and inducing a fast and sustained suppression of gonadotrophin secretion in rats and primates. One of the few animal models of prostate adenocarcinoma is the D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 35 publications
0
30
0
2
Order By: Relevance
“…В ис-следовании на животных дегареликс имел самую низкую актив-ность в отношении высвобождения гистамина среди всех проте-стированных антагонистов ЛГРГ. На ex vivo модели человеческой кожи показаны аналогичные результаты: дегареликс демонстри-ровал самую низкую склонность к высвобождению гистамина по сравнению с ганиреликсом, абареликсом и цетрореликсом [31,32,[38][39][40].…”
Section: исследования I фазыunclassified
“…В ис-следовании на животных дегареликс имел самую низкую актив-ность в отношении высвобождения гистамина среди всех проте-стированных антагонистов ЛГРГ. На ex vivo модели человеческой кожи показаны аналогичные результаты: дегареликс демонстри-ровал самую низкую склонность к высвобождению гистамина по сравнению с ганиреликсом, абареликсом и цетрореликсом [31,32,[38][39][40].…”
Section: исследования I фазыunclassified
“…Subcutaneous administration of degarelix allows the formation of a gel depot that facilitates sustained drug release [Princivalle et al 2007]. This is reflected in the prolonged LH and testosterone suppression associated with degarelix which, in comparative studies, displayed a longer duration of action than other GnRH antagonists (abarelix, cetrorelix, ganirelix, azaline B).…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Initially, preclinical study in rats suggested that rapid, profound and sustained testosterone suppression achieved with degarelix might result in greater suppression of tumor growth than is achieved with GnRH-A [33,34]. Those promising results have led to phase II/III clinical studies.…”
Section: B Gnrh Antagonist Therapymentioning
confidence: 99%